Efficacy of intervention towards blood donation to increase voluntary blood donation: a systematic review - Easmin, Fatema; Ashadul Islam, M.; Islam, Shariful; Rahman, Atiar; Sonia, Farah Anjum (International Journal of Research in Medical Sciences, 2024)
Although blood is the essence of life, and is one of the most precious donations; blood transfusion services are facing shortage of blood all over the world. A significant percentage of people have false beliefs about blood donation. Increase in the level of knowledge and correction of false beliefs should be the top most priority. Therefore, studying factors contributing to their knowledge, attitude and practice of blood donation is essential. There are studies that investigated the effectiveness of interventions or procedure changes in blood donation settings on outcomes including donor deferral, disclosure of risk factors, and rates of errors and omissions. Researchers also identified several interventions to improve donor compliance that have been tested in blood donation settings and provided evidence for the effectiveness of computerized interviews in improving detection of risk factors. Interventions can utilize the processes of change (POC) measure to guide stage matched interventions to encourage use of relevant experiential and behavioral strategies to increase blood donation. Interventions to recruit and retain blood donors in the general population have been classified into five approaches: motivational, reminders/asking, measurement of cognitions, incentives, and preventing vasovagal reactions. Effective recruitment and retention are two different processes and may require different approaches. For example, retention may be influenced more by interventions that focus on actions during or after donation rather than interventions prior to the blood donation appointment.